Pedagogic Paths to Liberation: Personal Struggles, Institution Building and the Rise of the Walter Rodney School of Groundings Praxis in Atlanta. (1st July 2018) - Benjamin, Jesse; Vaught, Seneca
Abstract : Dr. Seneca Vaught interviewed Dr. Jesse Benjamin about his personal pedagogical background and process, its intersections with activism and scholarship, and how this led him to working with the Walter Rodney Foundation and various associated projects in the Atlanta area. The discussion moves from research at a radical experimental Quaker international college, to activism and research in upstate New York, at Binghamton University, and finally to work as an engaged community professor in Atlanta. Also covered are the establishment of a Coloniality Research Working Group and a Walter Rodney Study Group in New York, and the influence of Sylvia Wynter. The discussion concludes with an overview of institution building activities in Atlanta, conjecturing the rise of Walter Rodney School of Praxis.